Acceptability and applicability of biometric iris scanning for the identification and follow up of highly mobile research participants living in fishing communities along the shores of Lake Victoria in Kenya, Tanzania, and Uganda. (April 2023) - Okello, Elialilia; Ayieko, Philip; Kwena, Zachary; Nanyonjo, Gertrude; Bahemuka, Ubaldo; Price, Matt; Bukusi, Elizabeth; Hashim, Ramadhan; Nakamanya, Sarah; Okech, Brenda; Kuteesa, Monica; Oketch, Bertha; et al.
Abstract: Background: Recruitment and retention of participants in research studies conducted in fishing communities remain a challenge because of population mobility. Reliable and acceptable methods for identifying and tracking participants taking part in HIV prevention and treatment research are needed. The study aims to assess the acceptability, and technical feasibility of iris scans as a biometric identification method for research participants in fishing communities. Methods: This was a cross-sectional study conducted in eight fishing communities in Kenya, Tanzania, and Uganda, with follow-up after one month in a randomly selected subset of participants. All consenting participants had their iris scanned and then responded to the survey. Results: 1, 199 participants were recruited. The median age was 33 [Interquartile range (IQR) 24–42] years; 56% were women. The overall acceptability of iris scanning was 99%, and the success rate was 98%. Eighty one percent (n = 949) had a successful scan on first attempt, 116 (10%) on second and 113 (9%) after more than two attempts. A month later, 30% (n = 341) of participants were followed up. The acceptability of repeat iris scanning was 99% (n = 340). All participants who accepted repeat iris scanning had successful scans, with 307 (90%) scans succeeding on first attempt; 25 (7%) on second attempt, and 8 (2%) after several attempts. The main reason for refusing iris scanning was fear of possible side effects of the scan on the eyes or body. Conclusion: The acceptability and applicability of biometric iris scan as a technique for unique identification of research participants is high in fishing communities. However, successful use of the iris scanning technology in research will require education regarding the safety of the procedure.